Nutriceral Buckwheat as a Potential Source of Nutrients - Kulla, Shreeja; Devi, T.Sucharita; Suneetha.W, Jessie; Gogoi, Moloya; Ahmed, Perves (Disease and Health: Research Developments Vol. 5, 2025)
Buckwheat (Fagopyrum esculentum), a pseudocereal from the Polygonaceae family, has emerged as a nutritionally and functionally significant crop. It is a good source of various vitamins and minerals, offering a well-balanced nutritional profile. Various bioactive compounds, such as phenolics, flavonoids (including orientin, quercetin, rutin, vitexin, isovitexin, and isoorientin), tannins, and steroids, contribute to therapeutic benefits. It offers numerous health benefits, including anti-inflammatory, anti-hemorrhagic, hypotensive, hypoglycemic, hypocholesterolemic, anticancer, anti-obesity, neuroprotective, cardiovascular, antioxidant, and blood vessel-protective effects. Thus, it is considered an alternative food component in the dietary treatment of chronic and metabolic diseases, such as diabetes, hypertension, and celiac disease. Additionally, its rich nutrient content supports a daily diet and promotes a healthier eating profile. Consequently, buckwheat is accepted as a functional food, recommended for improving human health, and used in the treatment of various diseases. Therefore, the nutritional profile and health benefits of buckwheat are documented.